Gertrude Stein's radio audience. Issue 12 (2nd December 2022) - Frank, Adam
ABSTRACT: This essay interprets Gertrude Stein's 1934 interview on NBC radio and its surrounding historical archive to unfold a powerful phantasy about radio audience as it simultaneously connects Stein to a new mass audience and frees her from it. In this phantasy, radio audience becomes the state of listening itself which takes place in the protected space of the studio while broadcasting becomes analogous to writing. The essay then turns to Theodor Adorno's contemporaneous work on 'radio physiognomics' in order to analyse his attempt to separate radio from its social ideals and the uses to which it has been put, and to supplement Adorno's Kleinian–Ferenczian approach to introjection, or the interiorisation of the microphone and the studio both in production and reception.